EEG Discontinuity and Neonatal Acidosis - J Gordon Millichap (Pediatric Neurology Briefs)
The effect of acidosis on cerebral function was evaluated by computerized online EEG monitoring in 14 ventilated preterm infants less than 32 weeks’ gestation at the Department of Paediatrics and Neonatal Medicine, Royal Postgraduate Medical School, Hammersmith Hospital, London, UK.